Oral colonization of Candida species in perinatally HIV-infected children in northern Thailand. - Pongsiriwet S. (2014)
Human immunodeficiency virus (HIV) infection remains a serious problem in northern Thailand. A high prevalence of perinatally HIV-infected children with oral candidiasis has been observed in the region. The objective of this study was to determine oral colonization of Candida spp. in children with perinatal HIV infection. Samples were collected by oral rinse or oral swab from 40 HIV-infected children and from 15 HIV-negative children as a control group. Yeasts recovered in culture were identified and quantified. The mean ages of HIV-infected children and HIV-negative children were 5.5 years (SD = 3.5) and 2.9 years (SD = 2.0) respectively. Eighteen HIV-infected children (45%) had clinical symptoms of oral candidiasis while none of the HIV-negative children had any such symptoms. By culture technique, yeasts were isolated from 28/40 (70%) of the HIV-infected children and 6/15 (40%) of the HIV-negative children. C. albicans was the most common species recovered from HIV-infected and HIV-negative children. Statistically, HIV infection was significantly associated with Candida spp. detection (P-value = 0.04). In contrast, the association between HIV infection and asymptomatic oral carriage of Candida spp. was not significant (P-value = 0.74). These findings demonstrate that oral colonization of Candida spp. is prevalent in HIV-infected children and suggest that prevention and treatment of oral candidiasis is needed for these children.